(untitled) (Yangi O’zbekiston taraqqiyotida tadqiqotlarni o’rni va rivojlanish omillari, 2024)
For governments looking to establish contemporary, effective, and transparent financial systems, FinTech's role in streamlining revenue collecting procedures is essential. As FinTech solutions continue to advance and gain traction, they have the potential to completely transform revenue collecting techniques and, in the process, improve the financial stability and sustainability of countries in the digital era.